2020
DOI: 10.1136/bmjopen-2019-036552
|View full text |Cite
|
Sign up to set email alerts
|

Women’s satisfaction with existing labour and delivery services in Ethiopia: a systematic review and meta-analysis

Abstract: ObjectiveTo estimate the pooled prevalence of women’s satisfaction with existing labour and delivery services in Ethiopia.DesignSystematic review and meta-analysis.MethodsMEDLINE/PubMed, Scopus, Hinari, Google Scholar and web of science electronic databases were searched for the study. This meta-analysis included nineteen cross-sectional studies. Cochrane I2 statistics were used to check the heterogeneity of the studies. Subgroup and sensitivity analysis were conducted with the evidence of heterogeneity. Egger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…Results from this study indicate that primiparity is a predictor of low birth satisfaction. This is in agreement with results from studies by Nahaee et al (Nahaee et al, 2020) (Fumagalli et al, 2021) and Ethiopia (Demis et al, 2020). Dystocia was also a predictor of low satisfaction in Nahaee et al's study (Nahaee et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Results from this study indicate that primiparity is a predictor of low birth satisfaction. This is in agreement with results from studies by Nahaee et al (Nahaee et al, 2020) (Fumagalli et al, 2021) and Ethiopia (Demis et al, 2020). Dystocia was also a predictor of low satisfaction in Nahaee et al's study (Nahaee et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Both of these facts may have a role in low birth satisfaction. In our study, long labor duration was a strong predictor of low birth satisfaction, which is in line with other studies conducted in Canada [40], Italy [13], and Ethiopia [41]. Dystocia was also a predictor of low satisfaction in Nahaee et al study [36].…”
Section: Discussionsupporting
confidence: 92%
“…
environment is expected to have the minimal medical standards that will guarantee clean delivery as well as a result of availability of equipment, medicine/supplies and skilled birth attendants [3,4,7,8]. Worldwide, statistics showed that about 2.5 million neonates died within the first 28 days of delivery [7]. It is reported that 2 in 3 neonates died within the first day of birth as a result of inadequate care during labour and delivery [7].
…”
mentioning
confidence: 99%
“…It is reported that 2 in 3 neonates died within the first day of birth as a result of inadequate care during labour and delivery [7]. In low and middle income countries where neonatal mortality statistics are abysmal, achieving perinatal survival devoid of morbidity will guarantee maternal satisfaction [7].Although the report of 2018 Nigeria Demographic Health Survey (NDHS) suggests that as much as 67% of women utilize Antenatal Care (ANC) services, only 39% of then deliver in a health facility where there is a Skill Birth Attendant (SBA) [9]. The poor rate of institutional deliveries shows that not all the women who are booked and attending antenatal care opt for institutional delivery [5].…”
mentioning
confidence: 99%